2022
DOI: 10.1101/2022.07.14.500125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epistasis reduces fitness costs of influenza A virus escape from stem-binding antibodies

Abstract: The hemagglutinin (HA) stem region is a major target of universal influenza vaccine efforts owing to the presence of highly conserved epitopes across multiple influenza A virus strains and subtypes. To explore the potential impact of vaccine-induced immunity targeting the HA stem, we examined the fitness effects of viral escape from stem-binding broadly neutralizing antibodies (stem-bnAbs). Recombinant viruses containing each individual antibody escape substitution showed diminished replication compared to wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Lee et al ( 52 ) recently reported that adsorptive mutations restore fitness to anti-stem mAb escape mutations localized in the selecting Ab epitope. Presumably, epistasis, in this case, is caused by alterations in HA receptor binding due to long-range conformational effects.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al ( 52 ) recently reported that adsorptive mutations restore fitness to anti-stem mAb escape mutations localized in the selecting Ab epitope. Presumably, epistasis, in this case, is caused by alterations in HA receptor binding due to long-range conformational effects.…”
Section: Discussionmentioning
confidence: 99%